Additive shaping object crack evaluation method, and crack evaluator

JP2025028001APending Publication Date: 2025-02-28PROTERIAL LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
JP2024131196
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2023-08-17
Filing Date
2024-08-07
Publication Date
2025-02-28

AI Technical Summary

Benefits of technology

【0015】 本発明によれば、付加造形法で造形した造形物の熱応力割れに対する割れ感受性を定量的に評価することができる。また、割れにくい造形条件や割れにくい組成を探索し選定することができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025028001000001_ABST
    Figure 2025028001000001_ABST
Patent Text Reader

Abstract

To solve the problem in which: when evaluating crack sensitivity of an additive shaping object, a quantitative evaluation is difficult, and, in particular, a composition hard to be cracked disables the evaluation.SOLUTION: A method, which evaluates crack sensitivity of an additive shaping object, is the additive shaping object evaluation method that has: an additive shaping step of, by use of raw material powder, additively shaping a crack evaluator having a body part, a pedestal part disposed facing the body part, a connection part connecting one end side of the body part and the pedestal part, a stress concentration part connecting the other end side of the body part and the pedestal part, and a comb teeth part connecting the body part and the pedestal part by comb teeth in between the connection part and the stress concentration part; and an evaluation step of evaluating crack sensitivity from cracked comb teeth occurring in the crack evaluator serving as an additive shaping object.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a method for evaluating cracks in an additively shaped object and a crack evaluator. [Background technology]

[0002] Among additive manufacturing processes, the LPBF (Laser Powder Bed Fusion) method, in which powder is laid out and selectively melted and solidified by a laser repeatedly, melts the powder with a laser, rapidly solidifies it, and forms the object, which is known to be susceptible to cracking due to tensile stress acting on the object caused by solidification shrinkage during rapid cooling and thermal shrinkage during cooling after modeling. The susceptibility of cracks caused by such tensile stress, that is, the cracking sensitivity to thermal stress cracking, varies depending on the composition of the raw material powder, the modeling conditions, the shape of the object, etc.

[0003] To create products or prototypes using the LPBF method, it is desirable to evaluate and understand the cracking susceptibility in advance and then select the composition of the raw powder, the molding conditions, the shape of the molded object, etc. Conventionally, one method for evaluating cracking is to cut the cross section of the molded object and polish the cut surface, but this has the problem of taking a long time to evaluate.

[0004] In the LPBF method, complex 3D objects are created by repeatedly laying out powder, selectively irradiating it with a laser, and melting and solidifying the powder. The irradiated laser is extremely fine, with a diameter of 50 to 150 μm, and the laser is scanned at a high speed of 500 to 2000 mm / s, resulting in localized melting and solidification, which tends to generate tensile stress in the object due to solidification shrinkage and thermal shrinkage caused by temperature drop. If this stress exceeds a certain threshold, cracks will occur. Since crack susceptibility differs depending on the powder composition, molding conditions, and shape of the object, a method for quantitatively and simply evaluating the influence of each has been desired.

[0005] As a simple method for evaluating crack susceptibility, Non-Patent Document 1 describes providing a notch in a molded object to make it more susceptible to cracking, and then changing the molding conditions to evaluate whether or not cracks occur. [Prior art documents] [Non-patent literature]

[0006] [Non-Patent Document 1] Stress relief technology using phase transformation in metal AM: Journal of Smart Processing, Vol. 10, No. 4 (July 2021) P. 163-170 Summary of the Invention [Problem to be solved by the invention]

[0007] The crack evaluation method disclosed in Non-Patent Document 1 proposes an evaluation shape of cracks by the LPBF method, but the evaluation is based on the form of cracks observed visually. For example, when changing the composition of a tool steel that is prone to cracking to develop a composition that does not crack, it is difficult to quantitatively evaluate the crack suppression effect of the composition change.

[0008] Therefore, the present invention aims to provide a crack evaluation method and a crack evaluator that can quantitatively evaluate the crack susceptibility to thermal stress cracking (hereinafter referred to as crack susceptibility) of objects formed by additive manufacturing methods such as the LPBF method, and can evaluate even compositions that are less likely to crack. [Means for solving the problem]

[0009] The present invention is a method for evaluating the crack susceptibility of an additively shaped object, comprising: an additive manufacturing process for additively manufacturing a crack evaluator using a raw material powder, the crack evaluator having a body portion, a base portion opposed to the body portion, a connection portion connecting one end side of the body portion and the base portion, a stress concentration portion connecting the other end side of the body portion and the base portion, and a comb tooth portion connecting the body portion and the base portion with comb teeth between the connection portion and the stress concentration portion; and an evaluation process for evaluating the crack susceptibility from cracked comb teeth generated in the crack evaluator, which is an additively shaped object. The present invention relates to a method for evaluating cracks in an additively formed object, the method comprising the steps of: As a result, even if the crack susceptibility of an additively shaped object is unknown, the crack susceptibility can be quantitatively evaluated from the number of broken comb teeth, etc. In the present invention, defects such as cracks and fissures are collectively called "cracks".

[0010] The evaluation step preferably evaluates the crack susceptibility from the relationship between the crack length obtained from the number of cracked comb teeth and the length of the body portion along the direction in which the comb teeth are arranged. This makes it possible to evaluate the crack susceptibility of even objects with a crack-resistant composition.

[0011] It is preferable that the evaluation step derives molding conditions with a lower susceptibility to cracking from a correlation between the crack length obtained from the number of broken comb teeth and the molding conditions. This makes it possible to explore and select molding conditions that are less likely to break.

[0012] It is preferable to derive an improved composition with lower cracking susceptibility from the evaluation results obtained in the evaluation process, use the improved composition in the additive modeling process, evaluate the cracking susceptibility of the modeled crack evaluator, and then repeat the evaluation of the improved composition and cracking susceptibility to derive a composition with lower cracking susceptibility. This makes it possible to search for and select compositions that are less likely to crack.

[0013] The present invention also relates to a crack evaluator for evaluating the crack susceptibility of an additively formed object, the crack evaluator comprising: a body portion; a base portion opposed to the body portion; a connection portion connecting one end side of the body portion to the base portion; a stress concentration portion connecting the other end side of the body portion to the base portion; and a comb tooth portion connecting the body portion and the base portion with comb teeth between the connection portion and the stress concentration portion.

[0014] It is preferable that the crack evaluator has a front curved surface on the other end side of the body portion, side curved surfaces on both sides of the front curved surface, and the front curved surfaces of the body portion and the comb tooth portion are connected via a stress concentration portion. Effect of the Invention

[0015] According to the present invention, it is possible to quantitatively evaluate the cracking susceptibility of an object produced by additive manufacturing to thermal stress cracking. Also, it is possible to search for and select molding conditions and compositions that are less likely to crack. [Brief description of the drawings]

[0016] [Figure 1] FIG. 1 is a perspective view of a CAD model of a crack evaluator. [Diagram 2] FIG. 2(a) is a front view and (b) is a side view of the crack evaluator. [Diagram 3] 3 is a cross-sectional view of FIG. 2 taken along line AB. [Figure 4] FIG. 4 is an enlarged cross-sectional view of part C in FIG. [Diagram 5] FIG. 1 is a flow diagram of a crack evaluation method. [Figure 6] This is a side photograph showing how the crack evaluator cracked at the comb tooth portion after being molded. [Figure 7] 1 is a graph showing the relationship between the length of a crack evaluator (additively shaped object) and the crack length in various alloys. [Figure 8] 1 is a graph showing the relationship between scanning speed and crack length in the shaping of tool steel. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0017] Hereinafter, an embodiment of the present invention will be described with reference to the drawings. [Crack evaluator] FIG. 1 shows a perspective view of a CAD model of a crack evaluator 10 according to one embodiment. The crack evaluator 10 is an additively shaped object composed of a body portion 1, a base portion 2, a connection portion 3, and a comb tooth portion 4. Additive shaping is performed toward the top of the page, first forming the base portion 2, then the comb tooth portion 4 and the connection portion 3, and finally forming the body portion 1. In this embodiment, the body portion 1 has a front curved surface 5, side curved surfaces 6, an upper flat surface 7, and a side flat surface 8 on both sides of the front curved surface 5, and the front curved surface 5 and the side curved surface 6 are shaped to be narrowed toward the base portion 2. The base portion 2 is flat. The body part 1 and the base part 2 are opposed to each other, one end of the body part 1 and the base part 2 are connected by the connection part 3, and the other end is connected by the stress concentration part 9 connected to the front curved surface 5 of the body part 1, and the body part 1 and the base part 2 are connected between the connection part 3 and the stress concentration part 9 by the comb tooth part 4 composed of a plurality of comb teeth 40 with a predetermined gap. That is, the integrally formed connection part 3, comb tooth part 4, and stress concentration part 9 are linearly arranged in this order. With this structure, when the body part 1 shrinks and deforms into a curved shape in the longitudinal direction during additive molding and / or when cooling to room temperature after molding, since one side in the longitudinal direction is fixed by the connection part 3, stress is concentrated in the stress concentration part 9 (also called the notch formation part) formed by the notch, and the comb tooth 40 at the end cracks and separates from this starting point. As the deformation progresses, cracks also occur in the adjacent comb teeth 40, and the cracks in the comb tooth part 4 progress. On the other hand, by providing a connection portion 3 that does not have gaps like the comb tooth portion 4 on the opposite side of the stress concentration portion 9, cracks are prevented from occurring from the comb teeth 40 in the vicinity of the connection portion 3. As a result, a composition with low cracking susceptibility will have a small number of cracks in the comb teeth, and a composition with high cracking susceptibility will have a large number of cracks in the comb teeth. In this way, even for additively shaped objects whose cracking susceptibility is unknown, the cracking susceptibility can be evaluated from the number of cracked comb teeth.

[0018] FIG. 2 shows (a) a front view and (b) a side view of a more specific embodiment of the crack evaluator. The body part 1 and the base part 2 extend in the longitudinal direction (length direction) and have a predetermined length L, a height of 16 mm, and a width of 10 mm. On the opposite side of the connection part 3 at one end of the body part 1, there is a front curved surface 5 in the shape of an arc with a front curvature radius R of 8 mm. This front curved surface 5 and the comb tooth part 4 are connected via a stress concentration part 9. By making the front curved surface 5 in the shape of an arc rather than a straight line, a larger stress is applied to the stress concentration part 9, making it easier to crack. In addition, on both sides of the short side direction (width direction) of the other end of the body part 1, side curved surfaces 6 with a curvature radius R of 8 mm are provided on the side surfaces in the longitudinal direction, and the side curved surfaces 6 and the comb tooth part 4 are connected at the lower part. This allows the width of the comb tooth part 4 to be narrowed to about 2 mm, making the comb tooth part 4 easier to crack. Also, by providing a side plane 8 with a height of 5 mm on the side of the body 1, the stress acting on the stress concentration portion 9 side is increased, making it easier to break. The length L of the body 1 and the length L of the base 2 may be different and can be designed appropriately.

[0019] The stress concentration portion 9 may be appropriately designed as long as it has a shape that concentrates stress. For example, it may be a narrow portion, a concave groove, a V-shape, a U-shape, etc., but it is preferable to have a sharply cut-out shape (hereinafter, the cut-out portion will be described as an example). FIG. 3 shows the AB cross section of FIG. 2. The cut-out shape is formed by the front curved surface 5 of the body portion 1 and the flat surface of the base portion 2 on the body portion 1 side. This cut-out portion 9 is provided at the end (lower end) of the connection surface between the base portion 2 and the comb-tooth portion 4. The cut-out portion 9 may be located at the end (upper end) of the connection surface between the comb-tooth portion 4 and the body portion 1. That is, it is sufficient to locate the cut-out portion 9 at a position where stress that becomes the starting point of cracks in the comb-tooth portion 4 is concentrated, and the same effect can be obtained.

[0020] Next, FIG. 4 shows an enlarged cross-sectional view of part C in FIG. 3. The comb teeth portion 4 connects the body portion 1 and the base portion 2 with a plurality of comb teeth 40. Here, a plurality of slits (gaps) 41 with a width of 0.3 mm are provided at a position 0.3 mm away from the cutout portion 9 through the comb teeth 40 with a width of 0.3 mm. By providing the slits 41, cracks are more likely to occur in the comb teeth portion 4, and cracks can be generated and evaluated even in compositions with low cracking susceptibility. In addition, a quantitative evaluation can be easily performed by counting the number of cracked comb teeth from the appearance. In addition, the cracking susceptibility can be evaluated in more detail from the appearance of the additively shaped object using a stereomicroscope. The shape, interval, width, height, etc. of the comb teeth and slits can be appropriately changed in design. For example, the comb teeth may be provided in multiple rows in the longitudinal direction, or may be provided in two rows. In this case, the comb teeth and slits may be arranged alternately. In addition, the shape of the slit does not have to be a rectangular parallelepiped, and may be appropriately changed to a cylindrical shape, an elliptical cylindrical shape, a triangular prism shape, etc.

[0021] [Crack evaluation method] A flow diagram of a crack evaluation method according to one embodiment of the present invention is shown in Fig. 5. This crack evaluation method evaluates the crack susceptibility of the raw material composition used in additive manufacturing by observing the crack morphology of the comb tooth portion 4, mainly the number of cracks in the comb teeth 40, when the above-mentioned crack evaluator 10 is actually additively manufactured, and the evaluation result is fed back to the raw material composition to improve the composition, and it can be used as a means for ultimately selecting a raw material composition that is less susceptible to cracking.

[0022] First, prepare raw powder of a specified composition (Step a). When additively manufacturing a product with new characteristics, the composition of the raw powder is determined by repeatedly making prototypes with the specified composition and improving them.

[0023] Then, the crack evaluator 10 is additively fabricated on the plate using the LPBF method or the like (step b). At this time, the fabrication conditions of the LPBF method are expressed by the following formula (1) as the correlation between the heat source energy density and the fabrication conditions. J = P / (v × a × t) (1) J: Heat source energy density (J / mm 3), P: laser or electron beam power (W), v: scanning speed (mm / s), a: scanning pitch (mm), t: layer thickness (mm) Therefore, the heat source energy density J can be controlled by changing the laser or electron beam output P, ​​the scanning speed v, the scanning pitch a, and the layer thickness t. The modeling parameters to be controlled are closely related to the laser or electron beam output P, ​​the scanning speed v, and the scanning pitch a, and it is preferable to control the heat source energy density by adjusting at least one of the above three parameters. Among them, adjusting the scanning speed v is effective and preferable.

[0024] Next, in the additive modeling process and / or the cooling process after additive modeling, the comb tooth portion 4 of the crack evaluator 10 is observed to see if any cracks have occurred (step c). In particular, since tensile stress acts significantly during cooling, it is advisable to visually check whether any cracks have occurred in the comb tooth portion, which is the additive modeling product after additive modeling. Here, it is sufficient to merely check the presence or absence of cracks, and it is not necessarily necessary to record and evaluate, for example, the number of cracked comb teeth. In addition, it is preferable to observe the comb tooth portion for cracks during the additive modeling process, but it is also sufficient to merely check the presence or absence of cracks here. In other words, this observation process may be omitted, in which the worker looks at the modeled product to the extent that he or she takes normal care during the modeling process during additive modeling or the subsequent cooling process, or looks at the degree of warping of the modeled product during the cooling process.

[0025] Next, the crack evaluator 10 and the plate are separated by wire cutting, and the crack evaluator 10, which is an additively shaped object, is taken out (step d).

[0026] Next, the number of cracks and the form of the cracks of the comb teeth of the crack evaluator 10 are observed and evaluated (step e). For observing the cracks, it is preferable to use an analysis device that can observe under magnification such as a stereomicroscope. In this process, the number of cracks in the comb teeth 40 are counted, the form of the cracks is observed, and the crack susceptibility of the raw material composition used is evaluated. For example, the evaluation means can simply evaluate from the number of cracked comb teeth. Also, the crack susceptibility can be evaluated from the correlation between the crack length obtained from the number of cracked comb teeth 40 and the predetermined length of the body part. At this time, the design of the stress concentration part (notch part) 9 and the comb teeth part 4 can be changed, that is, the applied stress can be changed to evaluate the crack susceptibility from a composition that is prone to cracking to a composition that is not prone to cracking. Also, it is possible to find appropriate molding conditions from the correlation between the crack length obtained from the number of cracked comb teeth 40 and the molding conditions during additive molding, and to search for molding conditions that are not prone to cracking. The case in which the process of searching for molding conditions that are not prone to cracking is also included in the method for evaluating cracks of an additively molded object of the present invention.

[0027] Then, the evaluation result is reflected in the design of the raw material composition, and the composition is improved and fed back to step (a) (step f). In the embodiment in which step f is provided, the evaluation result is fed back to the raw material composition to search for composition improvement. Therefore, an improved composition is designed from the evaluation result obtained in the evaluation process, and this improved composition is used in a new additive modeling process to form a new object, the crack susceptibility of the newly formed crack evaluator is evaluated, and the improved composition is fed back. This step is then appropriately repeated, that is, the development of the final powder composition is completed by repeating composition improvement and evaluation (step g). The case where a process of searching for a composition that is less likely to crack is also included in the method for evaluating cracks in an additively modeled object of the present invention. At this time, it is preferable to adjust at least one parameter of the laser or electron beam output P, ​​the scanning speed v, and the scanning pitch a, and find the optimal modeling conditions while evaluating them. EXAMPLES

[0028] The present invention will now be described in detail with reference to examples. Example 1 The crack evaluator 10 in FIG. 1 was additively manufactured by the LPBF method using raw powder with a composition of tool steel (JIS standard: SKD61) and an average particle size of 39 μm. The length L of the crack evaluator 10 was set to 35 mm. The manufacturing conditions were Ar atmosphere manufacturing, laser diameter 75 μm, layer thickness t 30 μm, scanning speed v 1000 mm / s, laser power P 180 W, and scanning pitch a 0.05 mm. As a result, warping occurred in the body part 1, and cracks occurred in the comb teeth part 4 near the pedestal part 2. Figure 6 shows a side photograph of the crack evaluator (additively manufactured object) after cooling. The crack susceptibility can be evaluated by the number of comb teeth that have cracks. In other words, the more cracks there are, the higher the crack susceptibility. In this example, the number of cracks was 32 when observed from one side curved surface 6, and 33 when observed from the opposite side curved surface 6. Here, the average value was taken and set to 32.5. Although the crack evaluator 10 has a symmetrical shape in the longitudinal direction, the number of cracks may appear different, so it is preferable to evaluate the number of cracks from both sides. In the method of Non-Patent Document 1, the evaluation was based on the presence or absence of cracks, but in this way, the present invention can perform a quantitative evaluation based on the number of cracked comb teeth.

[0029] Example 2 The correlation between the length L of the additively molded object of the crack evaluator 10 and the crack length was examined for each material type. Five types of compositions were compared: tool steel, maraging steel, SUS316 stainless steel, SUS630 stainless steel, and alloy 718. Tool steel was molded in two atmospheres, Ar and nitrogen. Other compositions were molded only in Ar atmosphere. Since the physical properties such as melting point differ for each composition, molding conditions were selected so that the internal void ratio was 0.1% or less. The same molding conditions as in Example 1 were used for tool steel, and the internal void ratio was 0.005%. Figure 7 shows the relationship between the length L of the crack evaluator (additively molded object) and the crack length for various alloys. The horizontal axis shows the effect of the length L of the crack evaluator 10 when it is set to 20 mm, 35 mm, and 50 mm. The vertical axis shows the crack length (mm). The crack length here was calculated by counting the number of cracked comb teeth 40 from each curved side under a magnified microscope, and multiplying the average number of cracked comb teeth by 0.6 mm. The reason for multiplying by 0.6 mm is that the width of the comb teeth 40 is 0.3 mm and the width of the slit 41 is 0.3 mm, so the total of 0.6 mm was used. In this example, the relationship between the length L of the crack evaluator and the evaluation of crack susceptibility is compared using the index of length to make it easier to understand. Therefore, it is preferable to unify the unit of the length L of the crack evaluator and the crack length in mm.

[0030] The results in FIG. 7 show that the longer the length L of the object formed as the crack evaluator 10, the more likely it is to crack. This is because the stress acting on the stress concentration portion 9 due to the deformation of the body portion 1 increases. Therefore, it can be said that it is easier to evaluate the crack susceptibility if the length of the crack evaluator 10 is designed to be relatively long. However, if the crack evaluator 10 is made too long, it will take longer to form, and more raw material powder will be required. Therefore, the length L of the crack evaluator is preferably about 20 to 50 mm.

[0031] In addition, in the comparison of compositions, the crack length was shorter in the order of tool steel, SUS630 stainless steel, SUS316 stainless steel, alloy 718, and maraging steel, showing a tendency to be less likely to crack. It is possible to quantitatively evaluate the crack susceptibility of various compositions, and this can be used as a criterion for composition selection. In particular, for materials that are less likely to crack, such as SUS316 stainless steel and alloy 718, it was difficult to find the occurrence of cracks using conventional methods, so it is extremely effective to be able to confirm them visually as in this embodiment. In this embodiment, it was not possible to confirm the occurrence of cracks in maraging steel, but it is possible to evaluate minute cracks by, for example, lengthening the crack evaluator or adjusting the shape of the notch or the interval between the slits. As described above, the crack susceptibility can be compared by evaluating the number of cracked comb teeth of each crack evaluator using multiple compositions. This allows easy quantitative evaluation of the difference in crack susceptibility due to differences in composition when developing materials with new compositions, and can be used to develop materials with lower crack susceptibility. For example, two types of powders with carbon amounts of 0.35 mass% and 0.4 mass% of the additive elements of tool steel are produced, and the crack evaluator 10 is manufactured using each powder under the same molding conditions. Then, the crack susceptibility affected by the carbon amount can be compared by examining the number of cracks in each comb tooth 40. Repeated evaluation of this process can be used to develop a composition of tool steel with lower crack susceptibility.

[0032] Furthermore, when tool steel was molded in an Ar atmosphere versus a nitrogen atmosphere, the nitrogen atmosphere tended to be more susceptible to cracking. This makes it possible to compare the differences between atmospheric gases. For example, if lowering cracking susceptibility is important, then printing can be done using expensive Ar gas. On the other hand, if increasing cracking susceptibility does not affect the properties of the molded object, then printing can be done using cheaper nitrogen gas. This can be used to differentiate between atmospheric gases.

[0033] Example 3 Next, the correlation between the crack length and the molding conditions was investigated. That is, the composition of the raw powder was tool steel (JIS standard: SKD61), molding was performed in an Ar atmosphere, the laser diameter was 75 μm, the layer thickness t was 30 μm, the laser output P was 180 W, the scanning pitch a was 0.05 mm, the length L of the molded object was 30 mm, and the scanning speed v was changed from 600 to 1400 mm / s. Figure 8 shows the relationship between the scanning speed and the crack length in the molding of tool steel. The horizontal axis is the scanning speed, and the vertical axis is the same crack length as in Figure 7. As a result, at a high scanning speed of 1000 to 1400 mm / s, the crack length was a high value of 18 to 20 mm. On the other hand, at a low scanning speed of 800 to 600 mm / s, the crack length was a low value of 11 to 13 mm. From this, it was found that the slower the scanning speed, the less likely the crack is to be broken. In addition to the scanning speed, it is possible to find a molding condition that suppresses the crack length by manipulating the output P of the laser or electron beam and the scanning pitch a. In this way, the present invention can be used to select a molding condition that suppresses cracks. [Explanation of symbols]

[0034] 1: body part, 2: base part, 3: connection part, 4: comb teeth part, 5: front curved surface, 6: side curved surface, 7: upper flat surface, 8: side flat surface, 9: stress concentration part (notch part), 10: crack evaluator, 40: comb teeth, 41: slit (gap)

Claims

1. A method for evaluating the crack susceptibility of an additively shaped object, comprising the steps of: an additive manufacturing process for additively manufacturing a crack evaluator using a raw material powder, the crack evaluator having a body portion, a base portion opposed to the body portion, a connection portion connecting one end side of the body portion and the base portion, a stress concentration portion connecting the other end side of the body portion and the base portion, and a comb tooth portion connecting the body portion and the base portion with comb teeth between the connection portion and the stress concentration portion; An evaluation step of evaluating crack susceptibility from cracked comb teeth generated in the crack evaluator which is an additively shaped object; A method for evaluating cracks in an additively shaped object, comprising:

2. 2. The method for evaluating cracks in an additively shaped object according to claim 1, wherein the evaluation step evaluates the crack susceptibility from a relationship between a crack length obtained from the number of broken comb teeth and a length of the body portion along a direction in which the comb teeth are arranged.

3. 3. The method for evaluating cracks in an additively molded object according to claim 1 or 2, wherein the evaluation step derives molding conditions with lower crack susceptibility from a correlation between the crack length obtained from the number of broken comb teeth and the molding conditions.

4. A method for evaluating cracks in an additively formed object as described in claim 1 or 2, characterized in that an improved composition with lower crack susceptibility is derived from the evaluation results obtained in the evaluation process, the improved composition is used in the additive modeling process to evaluate the crack susceptibility of the formed crack evaluator, and the evaluation of the improved composition and crack susceptibility is repeated to derive a composition with lower crack susceptibility.

5. A crack evaluator for evaluating the crack susceptibility of an additively shaped object, comprising: A crack evaluator comprising: a body portion; a base portion opposed to the body portion; a connection portion connecting one end side of the body portion to the base portion; a stress concentration portion connecting the other end side of the body portion to the base portion; and a comb tooth portion connecting the body portion and the base portion with comb teeth between the connection portion and the stress concentration portion.

6. The crack evaluator described in claim 5, characterized in that the other end of the body portion has a front curved surface, and side curved surfaces are provided on both sides of the front curved surface, and the front curved surface of the body portion and the comb tooth portion are connected via a stress concentration portion.